Tinjauan Pengajuan Kasasi Penuntut Umum Terhadap Pembebasan Terdakwa dari Dakwaan Primair dalam Perkara Korupsi - Dedhy Prabowo (Verstek, 2019)
This study aims to reviewing the suitability of the Cassation Appeal by the Public Prosecutor against the acquittal of the Defendant from the Primair indictment by the High Court Judges of Central Sulawesi Province in Palu in the Corruption Case as contained in the Supreme Court Decision of the Republic of Indonesia No. 134 K/PID.SUS/2014 with the fulfllment of The provisions of article 253 paragraph 1 of the Criminal Procedure Code. This research is Normative Law Research with case approach, that is to Case of Corruption of Banggai Regency Budget Fund that is General Allocation Fund (DAU) for Development of SDN. Trijadi in Luwuk with the defendant Beby Kobstan. Based on the results of the research and discussion that has been the author of the analysis, the Prosecutor was able to prove that the Cassation Appeal and the reasons for his Cassation have been in accordance with the provisions contained in Article 253 paragraph (1) of the Criminal Procedure Code, especially as clearly stated in letter a which determines whether A rule of law is not applied or implemented is not as it should be. The Cassation Reason that has been submitted by the Public Prosecutor in the Case of Corruption can be seen that Judex Factie does not apply or improperly implements a rule of law, namely in the case of a criminal imposition against Beby Kobstan which corroborates the decision of the District Court of Luwuk namely imprisonment for 1 (One) year is not or less fulflls the sense of justice in the community, since the Judge of the District Court Luwuk and the Court of Corruption at the Central Sulawesi High Court in Palu has taken over the whole prosecution of the Public Prosecutor Luwuk and stated that the Defendant Beby Kobstan has been proven Legitimate and convincing guilty of committing a criminal act of corruption.Keywords: Appeal, Indictment, Criminal Act of Corruption, Corruption.